TRANSFORMASI PEMBELAJARAN ILMU FALAK dI ERA INDUSTRI (Application and Inspiring Learning Methods) - Mursyid Fikri dan Baharuddin (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2021)
Abstrac The industry has experienced a very rapid revolution phase, namely industry 4.0, this has consequences for science and sharia education to be able to prepare individuals who have competence in facing various challenges in the future by applying or producing a work that is a symbol of scientific dialectics. This research is a library research using a descriptive qualitative method approach that connects the existing theory with the descriptive reality of astronomy today. Astrology is the most important part in the history of Islamic civilization. History has recorded that scholars and Al-Falaky (a title for astronomy activists) emerged when Islamic civilization was at its golden peak and when Islam experienced a decline, the echo of astronomy was no longer heard, even today many Muslims do not know the term "the science of astronomy". This phenomenon indicates that there is a positive correlation between the establishment of Islamic civilization and the development of Islam which is a symbol of astronomy science which is a reflection of the existence of Islam. Therefore, there is a need for a transformation/revolution of the astronomy learning movement that does not only revolve at the theoretical level, but also application and inspiring learning methods by utilizing the development of industrial media 4.0 to introduce astronomy and strengthen astronomy learning. The scientific transformation is at least able to touch three scientific dimensions, namely the intellectual dimension, the spiritual dimension and the socio-political dimension. Keywords: Transformation, Astrology Learning, industry 4.0.